Geographical Analysis of Domestic Violence in Baghdad Governorate (Journal of the College of Basic Education, 2026)
This study aims to conduct a comprehensive geographical analysis of the phenomenon of domestic violence in Baghdad Governorate, given its increasing rates and profound impact on individuals, families, and society. The study addresses the spatial distribution of domestic violence and the factors influencing it across the various geographical areas of the governorate. The study relies on a descriptive analytical approach, using a mixed methodology that combines quantitative and qualitative methods, including analyzing statistical data on domestic violence cases and conducting interviews with experts and victims. The primary objectives of the research are to identify the spatial patterns of domestic violence, understand its geographical determinants, and develop a spatial information system to support decision-makers in formulating effective strategies to combat this phenomenon.